Long-term hepatitis B virus infection of rhesus macaques requires suppression of host immunity - Sreya Biswas; Lauren N. Rust; Jochen M. Wettengel; Sofiya Yusova; Miranda Fischer; Julien N. Carson; Josie Johnson; Lei Wei; Trason Thode; Mohan R. Kaadige; Sunil Sharma; Majd Agbaria; et al. (Nature Communications, 2022)
Here, Biswas et al. present and characterize a second-generation model of HBV infection in rhesus macaques, showing that extended infection requires suppression of host immunity.